Pendampingan Santri Dalam Meningkatkan Pembelajaran Al-Qur’an Menggunakan Metode Ummi Di Desa Ciseureuh - Ismiati Ismiati; Usep Setiawan (Sivitas : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2023)
Residents with children in public schools are dissatisfied with the religious education materials taught in schools, the fact that schools are only responsible for executing the curriculum, and the fact that religious education is only taught for two hours each week. Meanwhile, religious education serves as the foundation for all of their actions and values in the future. And the school that parents entrust with their children's education falls short of expectations. The method employed in this service is Participatory Action Research (PAR), which involves approaching the children and parents of the Ciseureuh Permai housing community as a research source and object. By observing, interviewing, and documenting the current difficulties in a descriptive and systematic manner, as well as related to the learning of the Qur'an. The Ummi method's strengths and weaknesses are unique, making learning a difficulty. However, if there is a strong desire to succeed, the problem becomes a sacrifice in obtaining success. Another barrier to studying the Ummi method is that if there are students who do not enter or do not understand the lesson, the student must conduct drilling or special learning for the teacher so that the pupils truly understand and comprehend the material